The structural discrepancy between the small and large gut microbiota of Asiatic toad (Bufo gargarizans) during hibernation - Song, Xiaowei; Zhai, Yuanyuan; Song, Jinghan; Zhang, Jingwei; Li, Xiangzhen (Folia microbiologica, 2023)
Hibernating amphibians are suitable for the research on the adaptation of gut microbiota to long-term fasting and cold stresses. However, the previous studies mainly focus on the large or whole gut microbiota but not the small gut microbiota. To test the structural discrepancy between the small and large gut microbiota during hibernation, we performed two independent batches of 16S rRNA gene amplicon sequencing to profile the small and large gut microbiota of hibernating Asiatic toad (Bufo gargarizans) from two wild populations. Both batches of data revealed that Proteobacteria, Bacteroidetes, and Firmicutes were the three most dominant phyla in the small and large gut microbiota. Three core OTUs with 100% occurrence in all gut microbiotas were annotated as Pseudomonas. A significant structural discrepancy was detected between the small and large gut microbiota. For instance, Proteobacteria assembled in the small intestine with a higher proportion than it did in the large intestine, but Bacteroidetes and Firmicutes assembled in the large intestine with a higher proportion than they did in the small intestine. The large gut microbiota exhibited higher diversity than the small gut microbiota. Nevertheless, a severe batch effect existed in the structural analysis of the gut microbiotas. The large gut microbiota showed a better resistance to the batch effect than the small gut microbiota did. This study provides preliminary evidence that microbes assemble in the small and large intestines of amphibians with discrepant patterns during hibernation.
Keywords: Batch effect; Gastrointestinal Microbiome; Amphibian; Gut microbiome; hibernace; střevní mikroflóra; RNA ribozomální 16S; Animals; Bufonidae; Hibernation; ropuchy; zvířata; 16S rRNA; RNA, Ribosomal, 16S